Tailoring fund selection to diverse investors: integrating financial and sustainability performance - Sorrosal-Forradellas, Maria-Teresa; Fabregat-Aibar, Laura; Barberà-Mariné, Maria-Glòria; Terceño, Antonio (Journal of Business Economics and Management, 2025)
This study explores the integration of financial and Environmental, Social, and Governance (ESG) criteria in the evaluation of investment funds within the energy equity sector, considering both short and long-term investor perspectives. Based on the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), a multi-criteria decision model, this analysis includes scenarios tailored to investors prioritizing financial returns and those focused on sustainability. The findings reveal that investors’ subjective preferences influence fund rankings, highlighting the need for adaptive classification systems. Finally, a customizable investment tool aligned with diverse investor priorities is proposed.